2020
DOI: 10.14309/ajg.0000000000001111
|View full text |Cite
|
Sign up to set email alerts
|

Higher Postinduction Infliximab Concentrations Are Associated With Improved Clinical Outcomes in Fistulizing Crohn's Disease: An ACCENT-II Post Hoc Analysis

Abstract: INTRODUCTION: There are only limited data regarding the role of therapeutic drug monitoring in fistulizing Crohn's disease (CD). We investigated the association between both induction and maintenance serum infliximab concentrations and favorable therapeutic outcomes in patients with fistulizing CD. METHODS: This was a post hoc analysis of the ACCENT-II trial evaluating patients with fistulizing CD receiving induction (n = 282) and maintenance infliximab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 36 publications
1
32
0
1
Order By: Relevance
“…A post hoc analysis of ACCENT-II RCT (282 patients after induction therapy and 139 patients on maintenance therapy) recently published by Papamichael et al [ 48 ] demonstrated that higher concentrations of IFX at week 14 were independently associated with composite remission defined as complete fistula closure and CRP normalization at week 14 (OR: 2.32; 95% CI: 1.55–3.49; p < 0.001) and week 54 (OR: 2.05; 95% CI: 1.10–3.82; p = 0.023). IFX concentrations predictive of composite remission were ≥20.2 μg/mL, ≥15 μg/mL and ≥7.2 μg/mL at weeks 2, 6, and 14, respectively.…”
Section: Tdm and Perianal Fistulizing CDmentioning
confidence: 99%
“…A post hoc analysis of ACCENT-II RCT (282 patients after induction therapy and 139 patients on maintenance therapy) recently published by Papamichael et al [ 48 ] demonstrated that higher concentrations of IFX at week 14 were independently associated with composite remission defined as complete fistula closure and CRP normalization at week 14 (OR: 2.32; 95% CI: 1.55–3.49; p < 0.001) and week 54 (OR: 2.05; 95% CI: 1.10–3.82; p = 0.023). IFX concentrations predictive of composite remission were ≥20.2 μg/mL, ≥15 μg/mL and ≥7.2 μg/mL at weeks 2, 6, and 14, respectively.…”
Section: Tdm and Perianal Fistulizing CDmentioning
confidence: 99%
“…In iximab was the rst proved effective biologics in promoting and maintaining CD-related stula closure, supported by high-quality randomized controlled trials (RCTs) with the primary endpoint as stula closure 5,10 . According to a multicenter, double-blind RCT conducted by Daniel and his colleagues 5 , 40% of patients had complete stula response at week 54 after scheduled in iximab administration.…”
Section: Discussionmentioning
confidence: 99%
“…Adalimumab is effective in treating stulizing CD with lower grade evidence though 11 . A majority of studies, prospective or retrospective, reported 30-50% of patients achieved clinical stula remission after long-term anti-TNF therapies 5,10,12 . Our results showed that a relatively lower percentage (23%) of patients presented stula closure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the infliximab cut-off differed from one study to another, it appears that the target level should be higher for pCD than for luminal CD. A recent subgroup analysis of the ACCENT II trial showed that a higher infliximab concentration at week 14 was associated with a fistula response (odds ratio (OR) [95%CI]: 1.16 [1.02–1.32]; p ​= ​0.019) and a composite remission outcome (defined as complete fistula response plus the normalization of C-reactive protein (CRP) levels; OR: 2.32 [1.55–3.49]; p ​< ​0.001) at week 14 ( Papamichael et al., 2021 ). Higher infliximab concentrations at week 14 were also associated with the composite remission outcome at week 54 (OR: 2.05 [1.10–3.82]; p ​= ​0.023).…”
Section: Confirm the Failure Of Anti-tnf Treatmentmentioning
confidence: 99%